Improvements of bounds for the Sándor–Yang means - Wei-Mao Qian; Hui-Zuo Xu; Yu-Ming Chu (Journal of Inequalities and Applications, 2019)
Abstract In the article, we provide new bounds for two Sándor–Yang means in terms of the arithmetic and contraharmonic means. Our results are the improvements of the previously known results.